Experiences and perceptions of respectful maternity care among mothers during childbirth in health facilities of Eastern province of Rwanda: An appreciative inquiry. - Alice Muhayimana; Irene Josephine Kearns; Darius Gishoma; Olive Tengera; Thierry Claudien Uhawenimana (PLoS ONE)
Introduction The World Health Organization (WHO) has emphasized the importance of ensuring respectful and dignified childbirth experiences. However, many countries, including Rwanda, have documented negative experiences during childbirth. Identifying best practices can help uncover sustainable solutions for resource-limited settings rather than focusing solely on the challenges and negative aspects. This study aimed to explore and describe how mothers in Rwanda's Eastern Province perceived and valued their childbirth experiences during their most recent labour and delivery. Methods We conducted a qualitative, exploratory, descriptive study. Purposive sampling targeted mothers who reported receiving respectful care during labour and childbirth. We selected 30 mothers from five hospitals in the Eastern Province of Rwanda. Data collection involved in-depth interviews (IDIs) following the first four stages of the Appreciative Inquiry (AI) 5D cycle. We employed the thematic analysis and used NVivo 12 to organize codes and develop a codebook. Results Three main themes, each with subthemes, emerged from the analysis. The first theme, appreciated care, included compassionate care and emotional support, autonomy and self-determination, timely care, privacy and confidentiality, and a supportive environment. The second theme perceived respectful care, addressed the meaning of respectful care and the sources of the participants' satisfaction. The third theme, strategies for improvement, focused on increasing women's self-control, sustaining providers' positive behaviours, and fostering caring leadership. Participants described receiving compassionate, empathetic, and dignified care, with timely attention to their needs. They expressed satisfaction with the services provided, noting that healthcare providers were kind, polite, and dedicated, often going beyond their duties. Mothers recommended to be more involved in decision-making, maintaining an optimal environment for childbirth, and enhancing community trust and professionalism in maternity care. They also acknowledged their responsibility to ensure proper birth spacing. Conclusion The aspects of care the participants appreciated could be consistently maintained and promoted. There is a need to build on the progress made in delivering RMC to strengthen community trust and elevate expectations. Given the sensitive nature of RMC, we recommend conducting further studies using the Appreciative Inquiry approach.